THE EXISTENCE OF THE SOLUTION OF THE CAUСHI PROBLEM FOR NONLINEAR STOCHASTIC PARTIAL DIFFERENTIAL-DIFFERENCE EQUATIONS OF NEUTRAL TYPE WITH RANDOM EXTERNAL PERTURBANCES - Юрченко, Ігор (SWorldJournal, 2022)
The question of the existence of a solution of the Cauchy problem in the class of nonlinear stochastic differential-difference equations of neutral type in partial derivatives with respect to random external perturbations independent of the Wiener process